Tenecteplase vs Alteplase Before Endovascular Therapy in Basilar Artery Occlusion. (2nd March 2021) - Alemseged, Fana; Ng, Felix C.; Williams, Cameron; Puetz, Volker; Boulouis, Gregoire; Kleinig, Timothy John; Rocco, Alessandro; Wu, Teddy Y.; Shah, Darshan; Arba, Francesco; Kaiser, Daniel; Di Giuliano, Francesca; et al.
Abstract : Objective: To investigate the efficacy of tenecteplase (TNK), a genetically modified variant of alteplase with greater fibrin specificity and longer half-life than alteplase, prior to endovascular thrombectomy (EVT) in patients with basilar artery occlusion (BAO). Methods: To determine whether TNK is associated with better reperfusion rates than alteplase prior to EVT in BAO, clinical and procedural data of consecutive patients with BAO from the Basilar Artery Treatment and Management (BATMAN) registry and the Tenecteplase vs Alteplase before Endovascular Therapy for Ischemic Stroke (EXTEND-IA TNK) trial were retrospectively analyzed. Reperfusion >50% or absence of retrievable thrombus at the time of the initial angiogram was evaluated. Results: We included 110 patients with BAO treated with IV thrombolysis prior to EVT (mean age 69 [SD 14] years; median NIH Stroke Scale score 16 [interquartile range (IQR) 7–32]). Nineteen patients were thrombolysed with TNK (0.25 mg/kg or 0.40 mg/kg) and 91 with alteplase (0.9 mg/kg). Reperfusion >50% occurred in 26% (n = 5/19) of patients thrombolysed with TNK vs 7% (n = 6/91) thrombolysed with alteplase (risk ratio 4.0, 95% confidence interval 1.3–12; p = 0.02), despite shorter thrombolysis to arterial puncture time in the TNK-treated patients (48 [IQR 40–71] minutes) vs alteplase-treated patients (110 [IQR 51–185] minutes; p = 0.004). No difference in symptomatic intracranial hemorrhage was observed (0/19 [0%] TNK, 1/91 [1%] alteplase; p = 0.9). Conclusions: TNK may be associated with an increased rate of reperfusion in comparison with alteplase before EVT in BAO. Randomized controlled trials to compare TNK with alteplase in patients with BAO are warranted. Clinicaltrials.gov Identifiers: NCT02388061 and NCT03340493. Classification of Evidence: This study provides Class III evidence that TNK leads to higher reperfusion rates in comparison with alteplase prior to EVT in patients with BAO.